PEMBAGIAN WARIS TERHADAP PASANGAN MUSLIM YANG MEMILIKI PERJANJIAN PRA NIKAH - Khobir Abdul Zabar; Rahmi Zubaedah (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
Heirs are entitled to the possessions or relics of the deceased, and the division of the inheritance can mean the property to be Shared with the bereaved, and then the prenup is a covenant couples make in order to make a provision or something in their household. The writing USES normative legal research methods through literature studies. The study explains that, while the marriage covenant has been made, it cannot put off the liabilities of one another, especially in the division of the property, which, although there isa wealth separating agreement, only separates the congenital items, for the possessions obtained during the marriage, when one dies, the share of the heir to the marriage will go in accordance with the islamic scriptures. Key Words; Prenupial Agreements; Heirs; Islamic Law